Duration of Dual Antiplatelet Therapy After Implantation of Drug-Coated Balloon - Zhang, Yuxuan; Zhang, Xinyi; Dong, Qichao; Chen, Delong; Xu, Yi; Jiang, Jun (Frontiers in Cardiovascular Medicine, 2021)
The drug-coated balloon (DCB) is an emerging percutaneous coronary intervention device with theoretical advantages and promising results. Recent clinical observations have demonstrated that DCB tends to have a good efficacy and safety profile in treatment of in-stent restenosis (ISR) for both bare-metal and drug-eluting stents, de novo coronary artery disease and other situation, such as high bleeding risk, chronic total occlusion, and acute coronary syndrome. Dual antiplatelet therapy (DAPT) has become an essential medication in daily clinical practice, but the optimal duration of DAPT after implantation of a drug-coated balloon remains unknown. At the time of the first in-man implantation of the paclitaxel-DCB for treatment of ISR in 2006, the protocol-defined DAPT duration was only 1 month. Subsequently, DAPT duration was recommended in various trials ranging from 1 to 12 months. However, there is no randomized controlled trial (RCT) on the optimal duration of DAPT after DCB angioplasty. Current clinical guidelines normally recommend the duration of DAPT after DCB-only angioplasty based on data from RCT of optimal duration of DAPT after stenting. In this review, we summarize current clinical trials on DCB-only angioplasty in different types of coronary artery diseases and their stipulated duration of DAPT, and compare their clinical results such as restenosis, target lesion revascularization and stent thrombosis event. We hope this review can assist clinicians make reasonable decisions about the duration of DAPT after DCB implantation.